ECOLOGICAL JUSTICE AND WASTE GOVERNANCE IN SOUTH TANGERANG: A POLITICAL ECOLOGY ANALYSIS - Syarkawi; Zakaria Habib Al-Ra'zie; Pirma Windra (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2026)
This study analyzes the relationship between the state, society, and the private sector in waste management in South Tangerang City through the perspective of Political Ecology and public policy. This research is motivated by the urban waste crisis which is characterized by waste production of more than 1,000 tons per day, while the capacity of the Cipeucang Final Disposal Site (TPA) is only able to accommodate around 300–400 tons per day. In contrast to previous research that emphasized the technical aspects of waste management, this study focuses on power relations, ecological impact distribution, and dynamics of environmental policy implementation. The research uses a qualitative approach with a case study design through in-depth interviews, field observations, and documentation studies.  The results of the study show that the waste crisis in South Tangerang is a structural problem influenced by urbanization, weak institutional capacity, and inequality in environmental governance. Residents around the Cipeucang Landfill reported strong odors, environmental pollution, and decreased quality of life due to the excess capacity of the landfill. The research also found that there is a differentiation of waste management services between areas with high purchasing power and areas that are more marginalized. These conditions create spatial injustices, where certain groups obtain better environmental services, while communities around landfills bear a greater ecological burden. In addition, the policy of sanctions against waste management violations shows a tendency to individualize risks through the transfer of responsibility to the community when waste sorting facilities and 3R TPS are not adequately available. In Foucault's perspective, such policies serve as a mechanism of social discipline and control. This research confirms that urban waste management is a matter of ecological justice, environmental risk distribution, and democratic development governance.  Key words: Political Ecology, Public Policy, Waste Management, Regional Development, Environmental Governance